Captain Caution : A Chronicle of Arundel - Roberts, Kenneth, 1885-1957 (London Collins, 1949)
First mate strives to save his dead captain's daughter from villain holding her prisoner in England, during the War of 1812.
Keywords: United States -- Maine--Arundel -- Prisoners -- Dartmoor Prison